RISK BASED FINANCIAL FEASIBILITY ANALYSIS OF PT. XYZ REVITALIZATION PROJECT USING MONTE CARLO SIMULATION - AULIA ADIWIRANTO, HANIF
PT. XYZ is a state-owned enterprise that has ceased operations because of financial reasons. Its stakeholders decided to revitalize the enterprise through new business lines which is roving fiberglass and fiber reinforced pipes (FRP). Before the project could be commenced, there is a need for a feasibility study to determine the profitability of the project. This research is aimed to determine the feasibility of the revitalization project using financial models equipped with Monte Carlo simulation to account for fluctuations in the model’s components. First the business process is mapped with process classification framework (PCF) and then be used to identify financial components used for calculating financial parameters which is Net Present Value (NPV), Modified Internal Rate of Return (MIRR), and Payback Period (PBP). Fluctuations in the model have two sources which is stochastic variables and risk events. Stochastic variables is identified from the financial components and is modelled with a triangular distribution. Risk events is identified using Failure Mode and Effects Analysis (FMEA) from the business process and it is viewed in two dimensions, which is the frequency of the event with a bernoulli distribution and the impact it creates with a triangular distribution. The Monte Carlo simulation then takes a number repeatedly from the distributions to calculate financial parameters multiple times until it forms a distribution of the financial parameter’s values. From the financial parameter’s distribution, it then can be calculated the probability that the project is feasible. The project is considered feasible if the probability of feasibility from all of the financial parameter’s distribution exceeds 60%. Results shows that the probability of feasibility from NPV, MIRR, and PBP is 92.9%, 92.9%, and 86.7% respectively. Sensitivity analysis shows that fiberglass and FRP price is the most sensitive variable. Because the probability of feasibility from all of the financial parameter’s distribution exceeds 60%, the project is considered financially feasible.